Land management affects grass biomass in the Eucalyptus tetrodonta savannas of monsoonal Australia - BOWMAN, DAVID M.J.S; FRANKLIN, DONALD C; PRICE, OWEN F; BROOK, BARRY W (Austral ecology, 2007)
We surveyed herbaceous biomass across the range of Eucalyptus tetrodonta savannas in north-western Australia. Sample sites (n = 211) were stratified within four broad geographical regions characterized by different mixes of land management regimes. Grasses dominated (87% mean) the herbaceous biomass. After controlling for climatic and edaphic gradients, herbaceous biomass was highest in the Greater Darwin region (2.2 t ha⁻¹) which is managed predominantly by Europeans, and least under semi-traditional Aboriginal management in Arnhem Land region (1.1 t ha⁻¹). In the drier Gulf of Carpentaria and Kimberley regions, where a mix of Aboriginal, conservation and pastoral land uses occurs, fuel loads were higher than in Arnhem Land region but still considerably lower than around Darwin. Sarga was recorded in all regions except the Gulf of Carpentaria and had the highest biomass in Darwin (0.88 t ha⁻¹) and lowest biomass in the Kimberley (0.54 t ha⁻¹). The proportion of herbaceous biomass made up of perennial grasses was least in Darwin (17%) and greatest in the Gulf (77%) regions. We suggest that climate, soils and land management account for differences between the drier pastoral regions of the Gulf of Carpentaria and the Kimberley and the wet Greater Darwin region relative to the Arnhem Land region. The high frequency, and larger spatial scale, of fires in the Greater Darwin region relative to the Arnhem Land region underpins the contrasting trends in total herbaceous biomass and abundance of flammable annual grasses.